Dūangčhai nai song čham - Wachirālongkō̜n, King of Thailand, 1952-; Thongthō̜ng Čhanthrāngsu (Krung Thēp Mahā Nakhō̜n : Samnakphim Matichon, 2019)
Compilation of articles on history of coronation and loyalty to the monarchy.
In Thai.
Keywords: Wachirālongkō̜n, -- King of Thailand, 1952-; Chakri dynasty; Coronations -- Thailand; Thailand -- Kings and rulers; Thailand -- History